Systemic and transcriptional response to intermittent fasting and fasting-mimicking diet in mice - Helene Michenthaler; Kalina Duszka; Isabel Reinisch; Markus Galhuber; Elisabeth Moyschewitz; Sarah Stryeck; Tobias Madl; Andreas Prokesch; Jelena Krstic (BMC Biology)
Abstract Background Dietary restriction (DR) has multiple beneficial effects on health and longevity and can also improve the efficacy of certain therapies. Diets used to instigate DR are diverse and the corresponding response is not uniformly measured. We compared the systemic and liver-specific transcriptional response to intermittent fasting (IF) and commercially available fasting-mimicking diet (FMD) after short- and long-term use in C57BL/6 J mice. Results We show that neither DR regimen causes observable adverse effects in mice. The weight loss was limited to 20% and was quickly compensated during refeeding days. The slightly higher weight loss upon FMD versus IF correlated with stronger fasting response assessed by lower glucose levels and higher ketone body, free fatty acids and especially FGF21 concentrations in blood. RNA sequencing demonstrated similar transcriptional programs in the liver after both regimens, with PPARα signalling as top enriched pathway, while on individual gene level FMD more potently increased gluconeogenesis-related, and PPARα and p53 target gene expression compared to IF. Repeated IF induced similar transcriptional responses as acute IF. However, repeated cycles of FMD resulted in blunted expression of genes involved in ketogenesis and fatty acid oxidation. Conclusions Short-term FMD causes more pronounced changes in blood parameters and slightly higher weight loss than IF, while both activate similar pathways (particularly PPARα signalling) in the liver. On individual gene level FMD induces a stronger transcriptional response, whereas cyclic application blunts transcriptional upregulation of fatty acid oxidation and ketogenesis only in FMD. Hence, our comparative characterization of IF and FMD protocols renders both as effective DR regimens and serves as resource in the fasting research field.